‘ … por decir Dios Trino y Uno, dijo Dios tres y uno son cuatro’: the Christian Trinity and the multiplicity of Andean Deities: indigenous beliefs and the instruction of the Christian doctrine in Quechua. - Sáenz, Sabine Dedenbach-Salazar (Colonial Latin American Review, 2016)
In this paper I examine how Christian priests in the early colonial period in the Andes tried to communicate the Christian concept of the Trinity to the indigenous population, mainly through textual but also through visual means. On the basis of these sources, I will address the following questions: how did the priests present the concept in Quechua, one of the general languages of the Andes, in morphological, lexico-semantic and argumentative terms; how was the Trinity represented in painting and, could the Indians relate these explanations to something they were familiar with in their own religion? Answering these questions will provide us with hypotheses as to how the indigenous population might have understood this Christian concept, which, in turn may enable us to better understand modern Andean belief forms with respect to the Trinitarian concept, which I shall briefly discuss in the final section. On the whole, the evidence suggests that, whilst the Christians may have thought that they could explain their Trinity to the Andean people better by using the Quechua language, the adoption of Andean concepts and language resources resulted in different reception strategies, such as the accommodation of Christian beliefs in the Andean religious system, but also the creation of new hybrid concepts based on Amerindian as well as Christian belief forms.